Anthropometric parameters of obesity can be alternative biomarkers for the potential cardiac dysfunction in obese children - Sun, Jing; Wang, Li; Lin, Yingjiong; Liu, Yunfeng; Liu, Fei; Liu, Xumei; Dong, Wenyan; Cai, Wenqian; Chen, Huimin; Xiao, Minhua; Luo, Hongfeng; Liu, Xihong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Childhood obesity, as one of the potential risk factors of cardiovascular diseases, is closely related to the incidence of cardiovascular disease at a younger age and has become a public health concern. However, what the potential impact on the cardiovascular system of childhood obesity is still unclear. Here, we systematically evaluated the cardiovascular aspects of 79 obesity children and 161 normal weight children in Guangzhou of China by using the potential cardiovascular disease biomarkers. Compared to normal weight children, obesity group not only exhibited significantly higher level of creatine kinase(CK), lactate dehydrogenase(LHD), fms-like tyrosine kinase-1(s-Flt-1), high-sensitivity C-reactive protein(hs-CRP) and uric acid(UA) (P=0.0062, P=0.0012, P=0.0013, P=0.0225 and P<0.0001), but also show significantly higher diastolic blood pressure(P=0.0074) and heart rate(P=0.0049) in obesity children. Of 79 obese children, 40 were able to further assess cardiac function by color Doppler echocardiography. The results showed that there were significant differences between obesity and healthy group on interventricular septal wall thickness at end diastole(IVSd), left ventricular posterior wall thickness at end diastole(LVPWD) and Aortic Annulus(AO) (P< 0.0001, P=0.0003 and P< 0.0001), and 52.4% obesity children were described overall declination of left and/or right ventricular function. Correlation analysis found that the physical index of obesity not only significantly correlated with blood lipid index, but also exhibit more significant correlation with most of the parameters of cardiac dysfunction than blood lipid index. Therefore, our analysis revealed that not only the characteristic of cardiac diastolic dysfunction in obesity children in Guangzhou(China), but also indicated that the physical index of obesity as a potential biomarker to predict the risk of cardiac dysfunction in children with simple obesity.